2013
DOI: 10.1038/ncomms3897
|View full text |Cite
|
Sign up to set email alerts
|

KaiC intersubunit communication facilitates robustness of circadian rhythms in cyanobacteria

Abstract: The cyanobacterial circadian clock is the only model clock to have been reconstituted in vitro. KaiC, the central clock component, is a homohexameric ATPase with autokinase and autophosphatase activities. Changes in phosphorylation state have been proposed to switch KaiC’s activity between autokinase and autophosphatase. Here we analyse the molecular mechanism underlying the regulation of KaiC’s activity, in the context of its hexameric structure. We reconstitute KaiC hexamers containing different variant prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 62 publications
4
40
0
Order By: Relevance
“…Similar active site configurations in KaiC and F 1 -ATPase and the aforementioned lack of large conformational changes between the kinase and "phosphatase" states of KaiC are also in line with the ATP synthase mechanism of dephosphorylation (47). Lastly, hexameric assembly and kinase, ATP synthase, and ATPase all mapping to the same active sites at CII subunit interfaces are consistent with allosteric control of KaiA-stimulated KaiC phosphorylation (38) and with communication and cooperative effects between KaiC protomers (54).…”
Section: Kaic Architecturesupporting
confidence: 49%
See 1 more Smart Citation
“…Similar active site configurations in KaiC and F 1 -ATPase and the aforementioned lack of large conformational changes between the kinase and "phosphatase" states of KaiC are also in line with the ATP synthase mechanism of dephosphorylation (47). Lastly, hexameric assembly and kinase, ATP synthase, and ATPase all mapping to the same active sites at CII subunit interfaces are consistent with allosteric control of KaiA-stimulated KaiC phosphorylation (38) and with communication and cooperative effects between KaiC protomers (54).…”
Section: Kaic Architecturesupporting
confidence: 49%
“…However, gold labeling gave a clear answer, and these experiments were carried out with full-length KaiB and KaiC proteins from S. elongatus (55) that constitute the in vitro PTO together with KaiA and ATP/Mg 2ϩ . That KaiC His 6 tags may have introduced an artifact is unlikely because C-terminally His-tagged KaiC was used to reconstitute the PTO in the same fashion as WT KaiC (54). The earliest evidence for CII binding actually came from native PAGE experiments that used KaiB with full-length KaiC (Fig.…”
Section: Evidence That Supports Binding Of Kaib To Kaiciimentioning
confidence: 99%
“…However, it is not fully understood how these conformational changes enhance the reversal of autophosphorylation. Recently, we revealed that substitution of the catalytic carboxylates E77 and E78 to glutamine residues, which decreases the ATPase activity of CI, does not affect the profile of autodephosphorylation (23). Therefore, it is unlikely that these conformational changes facilitate the coupling of ATP hydrolysis in CI to formation of ATP by reversing autodephosphorylation in CII.…”
Section: Discussionmentioning
confidence: 99%
“…Each KaiC protomer follows a cycle comprising the four steps in the presence of interactions among hexamer subunits and between hexamers. Therefore, the reaction rate of each step can be affected by the phosphorylation of other KaiC protomers within the same hexamer or by another KaiC hexamer through competition for free KaiA (38). If the cycle of each KaiC phosphorylation proceeds synchronously, the ratio of KaiC phosphorylation oscillates with large amplitude.…”
Section: Discussionmentioning
confidence: 99%